Assignment of weight-based antibody units to a human antipneumococcal standard reference serum, lot 89-S. - Quataert, S A (1995)
A human reference serum pool, lot 89-S, has been developed for use in quantitating concentrations of antibody to Streptococcus pneumoniae. Weight-based units have been assigned to antibodies to 11 pneumococcal polysaccharide (PnPs) serotypes (1, 3, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F) by using enzyme-linked immunosorbent assay methodology and a human standard reference serum, USNRP IS 1644. The experimentally derived assignments for anti-PnPs antibodies of the immunoglobulin G (IgG), IgM, and IgA isotypes in lot 89-S correlate well to the separately determined immunoglobulin assignment. These assignments for this antipneumococcal standard serum were used to quantitate IgG, IgM, and IgA isotype levels and the total immunoglobulin level in pediatric samples from a pneumococcal conjugate vaccine trial. The data indicate that these assignments may be used to assess levels of antibody to PnPs serotypes in human serum.